2001
DOI: 10.1021/ie010242n
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Self-Polishing Antifouling Paints Using Rotary Experiments and Mathematical Modeling

Abstract: A detailed mathematical model for a self-polishing antifouling paint has been developed. The important rate-influencing steps, dissolution of pigment particles, hydrolysis and erosion of the active polymer binder, effective diffusion in the leached layer, and external mass transport of relevant species, were all included. The aims have been to produce a tool for estimating paint lifetimes at various seawater conditions and paint compositions, for possible product optimizations, and for supporting the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
100
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(104 citation statements)
references
References 23 publications
0
100
0
Order By: Relevance
“…Release of biocides from surfaces painted with antifouling paints is controlled by biocide chemistry, hydrodynamics, temperature, salinity, pH, microbial biofilm (Kiil et al, 2001(Kiil et al, , 2002Valkirs et al, 2003), and as shown here, painted material. When the mini-bars were removed from waters for sampling, we observed slight swelling of wood mini-bars.…”
Section: Effect Of Painted Materials On Cu Releasementioning
confidence: 71%
See 2 more Smart Citations
“…Release of biocides from surfaces painted with antifouling paints is controlled by biocide chemistry, hydrodynamics, temperature, salinity, pH, microbial biofilm (Kiil et al, 2001(Kiil et al, , 2002Valkirs et al, 2003), and as shown here, painted material. When the mini-bars were removed from waters for sampling, we observed slight swelling of wood mini-bars.…”
Section: Effect Of Painted Materials On Cu Releasementioning
confidence: 71%
“…(3) and (4)) (Ferry and Carritt, 1946;Kiil et al, 2001;Singh and Turner, 2009). In oxygenated water, Cu þ may be rapidly converted to cupric ion (Cu 2þ ) Kiil et al, 2001;Valkirs et al, 2003).…”
Section: Effect Of Salinity On Cu Releasementioning
confidence: 99%
See 1 more Smart Citation
“…This results in cleavage of the TBT portion from the copolymer, and releases the biocides into the water [74]. Once many TBT portions have been cleaved, the partially reacted brittle polymer backbone can be easily washed off by the moving seawater, which exposes a fresh coating surface (Figure 7(a),(b)) [74,78]. The hydrolysis process provides a low hull roughness (about 100 μm), so as not to increase the resistance of the ship's hull [1].…”
Section: Modern Chemical Antifouling Methodsmentioning
confidence: 99%
“…Rotor testing, in which paint samples are attached to a cylinder that is rotated at high speed in sea water, is commonly used for testing AF paints. The total run time of such tests is at least two months, but typically three to four months (Kiil et al 2001). Trentin et al (2001) have compared the results of rotor testing with extended exposure testing for conventional and selfpolishing paints containing cuprous oxide as biocide and found that laboratory tests proved to be significantly shorter, with a reduction in time from several years for field tests to just a few months and days for laboratory tests.…”
Section: (B) Biofilm Monitoringmentioning
confidence: 99%